2004
DOI: 10.1089/tmj.2004.10.170
|View full text |Cite
|
Sign up to set email alerts
|

Home Telehealth Reduces Healthcare Costs

Abstract: The aim of this study was to determine whether home telehealth, when integrated with the health facility's electronic medical record system, reduces healthcare costs and improves quality-of-life outcomes relative to usual home healthcare services for elderly high resource users with complex co-morbidities. Study patients were identified through the medical center's database. Intervention patients received home telehealth units that used standard phone lines to communicate with the hospital. FDA-approved periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(98 citation statements)
references
References 23 publications
1
94
1
2
Order By: Relevance
“…It enables healthcare professionals to maintain or even improve an end-user's condition and quality of life, and at the same time reduce in-hospital costs [20][21][22][23][24]. But, for a successful implementation, it seems essential that the users experience a good usability of such systems.…”
Section: Discussionmentioning
confidence: 99%
“…It enables healthcare professionals to maintain or even improve an end-user's condition and quality of life, and at the same time reduce in-hospital costs [20][21][22][23][24]. But, for a successful implementation, it seems essential that the users experience a good usability of such systems.…”
Section: Discussionmentioning
confidence: 99%
“…Because there are no published studies of the impact of telehome monitoring in patients with angina, comparisons cannot be made. Although both Noel et al 37 and Chumbler et al 38 studied mixed groups of patients, including those with heart disease, neither measured quality of life. Both did include measures of functional status; there were no differences between randomized groups in Noel and colleagues' 37 study, and intervention patients had better functional status than control patients in the latter study.…”
Section: Functional Status and Quality Of Lifementioning
confidence: 99%
“…Studies have also shown the effectiveness of telemedicine for a variety of chronic diseases care management such as: general health status monitoring (self-reported, or with home-based devices) with scheduled interventions such as nurse visit or GP consultation (video, telephone or physical attendance) [29,32,33,34,35,36]; medication compliance and modification, depending on symptoms and side effects, and the early detection of deterioration of patient leading to ‘just-in-time’ interventions, thereby preventing unnecessary admissions and escalating healthcare costs [37,38,39]. …”
Section: Discussionmentioning
confidence: 99%